Evaluating the Impact of Digital Technologies on Business Operations and Consumer Behaviour: A Sectoral Analysis - Kamya, Bhatt; Patel, Diya; Kachhadiya, Diya; Sharma, Yajurv; Chauhan, Rahul; Maseleno, Andino; Rizal Isnanto, R. (Dinasti Accounting Review, 2024)
This research investigates the impact of digital technologies on consumer behavior, organizational operations, and ethical considerations within various industries. Utilizing ANOVA tests, the study reveals significant gender differences in perceptions of technology's influence, particularly regarding ethical concerns and customer satisfaction. Findings indicate that while digital technologies have improved business operations, they also raise critical ethical issues such as data privacy and security. The research highlights the necessity for organizations to implement robust policies addressing these challenges to foster consumer trust and engagement. Future studies should explore the intersectionality of demographic factors and the long-term implications of emerging technologies. Overall, this study emphasizes the global impact of digital transformation and the importance of ethical practices in navigating the evolving digital landscape.